Climate Change and the Practice of Medicine: Essentials for Resident Education. (8th September 2020) - Philipsborn, Rebecca Pass; Sheffield, Perry; White, Andrew; Osta, Amanda; Anderson, Marsha S.; Bernstein, Aaron
Abstract : Despite calls for including content on climate change and its effect on health in curricula across the spectrum of medical education, no widely used resource exists to guide residency training programs in this effort. This lack of resources poses challenges for training program leaders seeking to incorporate evidence-based climate and health content into their curricula. Climate change increases risks of heat-related illness, infections, asthma, mental health disorders, poor perinatal outcomes, adverse experiences from trauma and displacement, and other harms. More numerous and increasingly dangerous natural disasters caused by climate change impair delivery of care by disrupting supply chains and compromising power supplies. Graduating trainees face a knowledge gap in understanding, managing, and mitigating these many-faceted consequences of climate change, which—expected to intensify in coming decades—will influence both the health of their patients and the health care they deliver. In this article, the authors propose a framework of climate change and health educational content for residents, including how climate change (1) harms health, (2) necessitates adaptation in clinical practice, and (3) undermines health care delivery. The authors propose not only learning objectives linked to the Accreditation Council for Graduate Medical Education core competencies for resident education but also learning formats and assessment strategies in each content area. They also present opportunities for implementation of climate and health education in residency training programs. Including this content in residency education will better prepare doctors to deliver anticipatory guidance to at-risk patients, manage those experiencing climate-related health effects, and reduce care disruptions during climate-driven extreme weather events.